Impact of random alloy fluctuations on inter-well transport in InGaN/GaN multi-quantum well systems: an atomistic non-equilibrium Green's function study. (29th October 2020) - O'Donovan, Michael; Luisier, Mathieu; O'Reilly, Eoin P; Schulz, Stefan
Abstract: Recent experimental studies indicate the presence of ballistic hole transport in InGaN multi quantum well (MQW) structures. Widely used drift–diffusion models cannot give insight into this question, since quantum mechanical effects, such as tunneling, are not included in such semi-classical approaches. Also atomistic effects, e.g. carrier localization effects and built-in field variations due to (random) alloy fluctuations, are often neglected in ballistic transport calculations on InGaN quantum well systems. In this work we use atomistic tight-binding theory in conjunction with a non-equilibrium Green's function approach to study electron and hole ballistic transport in InGaN MQW systems. Our results show that for electrons the alloy microstructure is of secondary importance for their ballistic transport properties, while for hole transport the situation is different. We observe for narrow barrier widths in an InGaN MQW system that (random) alloy fluctuations give rise to extra hole transmission channels when compared to a virtual crystal description of the same system. We attribute this effect to the situation that in the random alloy case, k ∥ -vector conservation is broken/relaxed and therefore the ballistic hole transport is increased. However, for wider barrier width this effect is strongly reduced, which is consistent with experimental studies. Our findings also provide a possible explanation for recent experimental results where alloying the barrier between the wells leads to enhanced ballistic (hole) transport in InGaN MQW systems.